2009
DOI: 10.1111/j.1467-2979.2009.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of learning in shark behaviour

Abstract: Introduction 451Learning terminology and early shark experiments 451Associative learning 452Non-associative learning 453Is there any evidence to suggest that sharks can use learning in natural situations? 453Migration, navigation and orientation 453Foraging 456 Social interactions 458Conspecifics/heterospecifics 458 AbstractThe role of learning in behaviour is well known for many animal taxa, including teleost fishes, insects, birds and mammals. However, its importance to sharks in everyday behavioural process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 166 publications
(315 reference statements)
2
67
0
1
Order By: Relevance
“…A series of binary choice experiments conducted with juvenile lemon sharks at the study site also found similar results, with smaller individuals (aged 0 to 1 yr) spending more time near a compartment with larger (aged 2 to 3 yr) sharks than size-matched conspecifics (Guttridge et al 2009a). We hypothesise that smaller sharks are willing to follow larger (older) individuals because the latter have accumulated more information about the habitat, predators and local prey (Guttridge et al 2009b). Associating with these larger individuals could facilitate the transfer of this information.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A series of binary choice experiments conducted with juvenile lemon sharks at the study site also found similar results, with smaller individuals (aged 0 to 1 yr) spending more time near a compartment with larger (aged 2 to 3 yr) sharks than size-matched conspecifics (Guttridge et al 2009a). We hypothesise that smaller sharks are willing to follow larger (older) individuals because the latter have accumulated more information about the habitat, predators and local prey (Guttridge et al 2009b). Associating with these larger individuals could facilitate the transfer of this information.…”
Section: Discussionsupporting
confidence: 52%
“…For teleost fishes this phenomenon is well studied (Griffiths 2003) and recent evidence has indicated that social recognition is a complex subject with species and populations capable of different levels of recognition (Ward et al 2009). As far as we are aware, this phenomenon has not been explored in sharks (Guttridge et al 2009b) and warrants investigation in the context of behavioural processes, such as foraging, navigation and reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…However where rewards are made readily available and there is a definite learning effect, greater risks of altering behaviour of target animals are likely to occur [22]. During the implementation of hand-feeding, the sharks easily identify the end of the arms (the hands) as a potential source of food.…”
Section: Specific Effects Of 'Hand-feeding' On Shark Behaviourmentioning
confidence: 99%
“…For the sharks' ability to make associations and behave accordingly, to learn, memorize, use tools, and for the ability of young sharks to use socially-acquired information about new elements in the environment, see Guttridge et al (2009;, Guttridge & Brown (2014), Schluessel (2015. 36 The syntheses seldomly belong to field researchers, though when that happens they are, in general, more assertive.…”
Section: Homo Sapiens Sapiens (Prima Sum: Primatum Nil a Me Alienum Pmentioning
confidence: 99%